2007
DOI: 10.1002/j.2333-8504.2007.tb02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Monotone Properties of a General Diagnostic Model

Abstract: ETS and the ETS logo are registered trademarks of Educational Testing Service (ETS). AbstractMonotonicity properties of a general diagnostic model (GDM) are considered in this paper. Simple data summaries are identified to inform about the ordered categories of latent traits. The findings are very much in accordance with the statements made about the GPCM (Hemker, Sijtsma, Molenaar, & Junker, 1996, 1997. On the one hand, by fitting a GDM with equal slopes across items, the observed total score X + = j:q jk =1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…For instance, recently, Xu (2007) conducted an investigation to examine whether the monotonicity property can generally be sustained in GDM so that simple data summaries (e.g., the observed total score) can help inform the ordered categories of the latent trait and lead to the reporting of valid and reliable scaled scores. Obviously, in recent years, a parametrically complex IRT modeling framework has been called for.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For instance, recently, Xu (2007) conducted an investigation to examine whether the monotonicity property can generally be sustained in GDM so that simple data summaries (e.g., the observed total score) can help inform the ordered categories of the latent trait and lead to the reporting of valid and reliable scaled scores. Obviously, in recent years, a parametrically complex IRT modeling framework has been called for.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…He demonstrated the model using simulated as well as TOEFL iBT data. Xu (2007) Simulation studies demonstrated the accuracy of the estimation procedure, and effectiveness of model fitting and model fit evaluation procedures. They concluded that the model is a promising tool for skills diagnosis that merits further research and development.…”
Section: Peter Vanmentioning
confidence: 94%
“…Any linking procedure is viewed as a restriction on the item parameter space, and then rewriting the log-likelihood function together with implementation of a maximization procedure under linear or nonlinear restrictions accomplishes the linking. Xu andM. von Davier (2008c/2008d) developed an IRT linking approach for use with the GD model and applied the proposed approach to NAEP data.…”
Section: Peter Vanmentioning
confidence: 99%
“…Specifically, simple data summaries were identified by Junker and Sijtsma to inform about the presence or absence of cognitive attributes when the full computational power needed to estimate the models is not available. Xu (2007) examined the stochastic ordering and monotonicity properties of a special case of GDM. Monotonicity of item response functions under DCMs will likely need further attention if we would like to enhance the interpretability of ability estimates or attribute estimates from such models.…”
Section: Issues With Dcms and Their Applicationsmentioning
confidence: 99%